A Geospatial Bibliometric Review of the HIV/AIDS Epidemic in the Russian Federation - Gray Neils, Megan E.; Pfaeffle, Herman O. I.; Kulatti, Art T.; Titova, Alena; Lyles, Galina S.; Plotnikova, Yulia; Zorkaltseva, Elena; Ogarkov, Oleg B.; Vitko, Serhiy M.; Dillingham, Rebecca A.; Heysell, Scott K. (Frontiers in Public Health, 2020)
Background: Increasing rates of HIV/AIDS in Eastern Europe and Central Asia contrast global trends, but the scope of HIV/AIDS research originating from Russian Federation and countries of the former Soviet Union has not been quantified. Methods: We searched six major scientific databases in Russian and English languages with medical subject heading terms “HIV” or “AIDS” and “Russia” or “Soviet Union” from 1991 to 2016. Each abstract indexed was reviewed and tagged for 25 HIV/AIDS research themes, location of research focus and first author. Results and Discussion: A total of 2,868 articles were included; 2,156 (75.1%) and 712 (24.8%) described research in the Russian Federation and countries of the former Soviet Union, respectively. There were 15 publications per million population in Russian Federation. Federal districts of the Russian Federation with the highest rates of HIV had the most limited publications. An interactive web-map with time-lapse features and links to primary literature was created using ArcGIS® technology [http://arcg.is/2FUIJ5v]. Conclusion: We found a lower than expected publication rate in the Russian Federation relative to rising HIV prevalence. The greatest deficits were in the most HIV burdened regions in the Russian Federation. Our findings highlight opportunities for new research strategies and public health efforts among key populations and subnational regions.